2017
DOI: 10.1111/aje.12410
|View full text |Cite
|
Sign up to set email alerts
|

Resource selection, utilization and seasons influence spatial distribution of ungulates in the western Serengeti National Park

Abstract: Understanding herbivore selection and utilization of vegetation types is fundamental to conservation of multispecies communities. We tested three hypotheses for how ungulate species select their habitats and how this changes with season: first, resources are distributed as a mosaic of patches so that ungulates are also distributed patchily; this distribution reflects habitat selection, which changes with season, the different ungulates behaving differently. Second, resources become scarcer in the dry season re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…They are also consistent with seasonal variation in the mechanism of herbivore coexistence, with more niche separation occurring in winter during times of low forage availability. Tooth wear studies have suggested seasonally-based resource partitioning (Rivals et al, 2009Rivals and Lister, 2016), as has been observed for some modern African savannah species (Bukombe et al, 2017;Kleynhans et al, 2011;Prins et al, 2006) and suggested for some Brazilian Pleistocene megaherbivores (Dantas et al, 2017). It is possible that competitive exclusion occurred during winter periods of resource scarcity and that species had overlapping niches during the rest of the year.…”
Section: Functional Redundancy and Resource Partitioningmentioning
confidence: 74%
See 2 more Smart Citations
“…They are also consistent with seasonal variation in the mechanism of herbivore coexistence, with more niche separation occurring in winter during times of low forage availability. Tooth wear studies have suggested seasonally-based resource partitioning (Rivals et al, 2009Rivals and Lister, 2016), as has been observed for some modern African savannah species (Bukombe et al, 2017;Kleynhans et al, 2011;Prins et al, 2006) and suggested for some Brazilian Pleistocene megaherbivores (Dantas et al, 2017). It is possible that competitive exclusion occurred during winter periods of resource scarcity and that species had overlapping niches during the rest of the year.…”
Section: Functional Redundancy and Resource Partitioningmentioning
confidence: 74%
“…African savannah herbivores exhibit lower dietary and niche separation during seasons of high plant productivity and greater niche separation during the low productivity dry season (Bukombe et al, 2017;Kleynhans et al, 2011;Prins et al, 2006). Experimental removal studies of herbivores in the African savannah did not observe complete functional redundancy between species, but there was functional redundancy for some response variables, such as vegetation height (Goheen et al, 2013;Pringle et al, 2014;van der Plas et al, 2016).…”
Section: Niche Separation and Functional Redundancymentioning
confidence: 97%
See 1 more Smart Citation
“…Water, food and cover are important factors influencing distribution of animals (Afolayan, Milligan, & Salami, ), and wetlands offer these basic necessities. Threat of dehydration, starvation and mortality in the dry season can cause movements from upland areas of dried and depleted forage to wetland buffer zone (Fynn et al, ; Girma, Mamo, & Ersado, ; Jenkins, Corti, Fanning, & Roettcher, ; Macandza, Owen‐Smith, & Cain, ; Owen‐Smith, ; Stacie, Erek, Nabil, Dhaval, & Bruce, ; Yaba, Mekonen, Bekele, & Malcolm, ), suggesting that wetlands are important for sustaining herbivore nutrition over the dry seasons (Bukombe et al, ; Grant & Scholes, ; Hopcraft, Olff, & Sinclair, ; Parrini & Owen‐Smith, ) and influencing their assemblages across wetlands. Wetlands also enable mammals to achieve thermoregulation via bathing pools and mud wallows.…”
Section: Resultsmentioning
confidence: 99%
“…The impala prefers open habitats (Estes 1991, Fritz & Bourgarel 2013), avoiding dense woodlands (Bukombe et al . 2017) and tall unburnt grasslands (Rduch 2016), as an anti-predator strategy (Anderson et al . 2010).…”
Section: Discussionmentioning
confidence: 99%